ENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING ( CPS ) TERHADAP HASIL BELAJAR SENI RUPA - Drs. Yusron Wikarya, M.Pd., KURNIA FAJRI, Drs. Abd. Hafiz, M.Pd, (Serupa The Journal of Art Education, 2016)
This study aims to determine the effect of applying the learning model creative problem solving (CPS) on learning outcomes art class VII SMPN 10 Padang. The data analysis technique is descriptive analysis and inductive analysis that normality test, homogeneous, variations and test t.Hasil research shows that the average value of 74.06 experimental class and control class 65.80. From the results of hypothesis test obtained t hit 4.10 and 1.96 with Î± t tab 0.05. So hit t> t tab, then Ho is rejected, so that there is a significant difference learning outcomes art using model CPS by conventional methods. The findings show the learning outcomes in the classroom who apply CPS is higher than the class that uses the conventional model.Kata kunci: hasil belajar, model pembelajaran CPS